Land tenure and farm management efficiency: the case of paddy and cinnamon production in customary land areas of Sumatra - Suyanto, S.; Tomich, Thomas P.; Otsuka, Keijiro (Wiley, 2001)
This study attempts to identify the impacts of land tenure institutions on the efficiency of farm management based on a case study of lowland paddy (rice) and upland cinnamon production in customary land areas of Sumatra. While the traditional joint‐family ownership system is found to exist in paddy land, more individualised ownership systems are widely observed in upland areas. Yet, we found no statistical evidence that residual profit per unit of land is affected by land tenure institutions in either the lowlands or uplands, indicating that the prevailing land tenure institutions are equally conducive to efficient farm management.